A vision for an academic health science centre: A survey of research engagement and barriers - Gerry Hughes; Claire Temple; Marie E. Ward; Cormac Kennedy; David Kevans; Derval Reidy; Jeremy Towns; Edel O’ Dea; Kishor Santhosh; Catherine Ludden; Mary Day; Martina Hennessy (PLoS ONE, 2026)
Background Integrating clinical research within patient care environments has been shown to enhance patient outcomes, foster a culture of clinical inquiry among staff, and improve hospital efficiency. This study aimed to evaluate the self-reported knowledge, beliefs and attitudes of hospital staff to organisational research and innovation at a large inner-city tertiary referral centre in Dublin, Ireland. The hospital is undergoing a physical and service expansion on its journey to becoming an academic health science centre. Methods A 26-item semi-qualitative survey, iteratively refined by the hospital Research Steering Committee, was disseminated to hospital staff through electronic and face-to-face recruitment, achieving 640 responses. Quantitative data were analysed in R and Microsoft Excel. Content analysis was carried out on qualitative data. Results Findings revealed that while most staff recognise the clinical value of research and have engaged in research activities, important barriers exist. Predominant challenges include time constraints, limited research support, and inadequate resources. Despite these barriers, over half of the respondents expressed a strong interest in additional research training, emphasising the need for structured support, including protected time for research, statistical assistance, and enhanced patient engagement initiatives. Discussion The results highlight both strengths and limitations within the hospital’s current research culture. While a positive foundation exists, with evident interest in research among staff, infrastructural and logistical gaps must be addressed to facilitate greater engagement. Targeted interventions, such as streamlined research approval processes, resource allocation, and strategic support for multidisciplinary collaboration, could enhance the hospital’s capacity to integrate research into clinical practice. These findings contribute to the ongoing discourse on embedding research in healthcare systems, underscoring the pivotal role of institutional commitment in nurturing a sustainable research culture.